LEGAL PROTECTION PROBLEM OF WIFE AND CHILDREN OF POLYGAMY SIRRI IN INDONESIA - Muhlas Muhlas; Gunarto Gunarto; Akhmad Khisni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In order to ensure that the marriage of a citizen to the full protection of the State shall be recorded, the marriage already recorded shall in addition to obtaining legal force and assurance of legal certainty shall also ensure the legal rights of both the spouse and the child and of the marriage concerned that. Unmarried marriages will not have any protection and legal guarantees, so married couples and children born from unregistered marriages are always unable to access public services, whereas they are citizens who are constitutionally protected and have no discrimination. The state has given the rules in the form of law or other written regulations to be implemented by its citizens, but the facts on the ground there are still many people who are not obedient, many examples of marriage monogamy or polygamy is not recorded (layman's term called marriage Under the hand / sirri). Parties who are very loss in marriage are not recorded are women and children are born right, because for him does not have a clear legal basis. The purpose of the law is to give goodness and benefit to human beings, referring to the objective of Islamic law that in emergency / dhorury the rights of principle must come to the masses of people (for life, religion, descent, property and soul / mind); Whereas from marriage that is not recorded will be born human also. In principle the fifth principle of right must be owned by humans, then whatever the condition of married citizens are not recorded both monogamy and polygamy should be sought legal solution in order to get their legal protection as a citizen.